Exploring non-linear internationalization processes in Portuguese firms - Coelho, J. V. (BAM 2023 Conference Proceedings, 2023)
This article presents the results of a 3-year study focused on exploring firm internationalization logics currently observable in Portugal, in three contributing sectors-Retail, Construction and ICT-Software Development. The rising number of Portuguese companies with international operations and growing sectoral diversification has been contributing to the recent international expansion of the Portuguese economy. It is important to introduce nuances in these recent developments, as the proportion of international firms and international expansion capabilities are still low. Results present domestic markets has having a diffluent role, opportunistic client or partner-following being adopted as dominant expansion logics, and indicate that internationalization processes are valued for their portability and reversibility. Room exists for de-and re-internationalization, resource commitment shifts and non-linear logics, an expression of managerial attempts to leverage resource constraints and exposure to risk and market uncertainty. Sectoral diversification and the deployment of more flexible organizational modes in internationalizing companies or company groups in Portugal are suggested as relevant and feasible paths to follow, given the different modal forms currently available for most companies to expand.